2012
DOI: 10.1186/1423-0127-19-58
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic lactobacillus and estrogen effects on vaginal epithelial gene expression responses to Candida albicans

Abstract: BackgroundVaginal epithelial cells have receptors, signal transduction mechanisms, and cytokine secretion capabilities to recruit host defenses against Candida albicans infections. This research evaluates how probiotic lactobacilli affect the defensive epithelial response.MethodsThis study used quantitative reverse transcription-polymerase chain reaction assay (qRT-PCR), flow cytometry, and a multiplex immunoassay to observe changes in the regulation of gene expression related to cytokine responses in the VK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 21 publications
2
68
1
6
Order By: Relevance
“…Pretreatment of pregnant CD-1 mice with L. rhamnosus GR-1 culture supernatant decreases lipopolysaccharide (LPS)-induced production of various cytokines and chemokines (4). Lactobacillus rhamnosus GR-1 suppresses expression of nuclear factor (NF)-B-related inflammatory genes and activates alternate mitogen-activated protein kinase (MAPK) and activator protein 1 pathways to recruit host defense factors in Candida albicans infection (5). Although several possible mechanisms underlying the beneficial effects of L. rhamnosus have been investigated, including direct antimicrobial action, as well as competitive exclusion of pathogens or inhibition of pathogen adhesion, enhancement of epithelial barrier function, and modulation of both local and systemic host immune responses (6), our previous studies demonstrated that pretreatment with high doses of L. rhamnosus may counteract the preventative effects (7,8).…”
mentioning
confidence: 99%
“…Pretreatment of pregnant CD-1 mice with L. rhamnosus GR-1 culture supernatant decreases lipopolysaccharide (LPS)-induced production of various cytokines and chemokines (4). Lactobacillus rhamnosus GR-1 suppresses expression of nuclear factor (NF)-B-related inflammatory genes and activates alternate mitogen-activated protein kinase (MAPK) and activator protein 1 pathways to recruit host defense factors in Candida albicans infection (5). Although several possible mechanisms underlying the beneficial effects of L. rhamnosus have been investigated, including direct antimicrobial action, as well as competitive exclusion of pathogens or inhibition of pathogen adhesion, enhancement of epithelial barrier function, and modulation of both local and systemic host immune responses (6), our previous studies demonstrated that pretreatment with high doses of L. rhamnosus may counteract the preventative effects (7,8).…”
mentioning
confidence: 99%
“…The latter effect might explain the increased cure of the disease when probiotic and antifungal therapies were conjointly administered (Martinez et al 2009b). Confirmatory studies have shown that L. rhamnosus can inhibit Candida biofilms through reduced hyphal differentiation (Matsubara et al 2016) and activation of IL-1␣ and IL-1␤ expression by an alternate signal transduction pathway (Wagner and Johnson 2012).…”
Section: Lactobacilli Properties and Early Evidence Of Benefits In Humentioning
confidence: 99%
“…Observa-se uma associação entre a presença de lactobacilos na vagina e a redução do desenvolvimento de candidíase vulvovaginal. Uma avaliação de como os probióticos lactobacilos afetavam a resposta epitelial defensiva sugere que os lactobacilos suprimem a expressão de genes inflamatórios induzidos por Candida albicans, modulando a resposta imunológica do hospedeiro 5 .…”
Section: Introductionunclassified